Structural heterogeneity in microcrystalline ubiquitin studied by solid‐state NMR. (16th March 2015) - Fasshuber, Hannes Klaus; Lakomek, Nils‐Alexander; Habenstein, Birgit; Loquet, Antoine; Shi, Chaowei; Giller, Karin; Wolff, Sebastian; Becker, Stefan; Lange, Adam
Abstract: By applying [1‐ 13 C]‐ and [2‐ 13 C]‐glucose labeling schemes to the folded globular protein ubiquitin, a strong reduction of spectral crowding and increase in resolution in solid‐state NMR (ssNMR) spectra could be achieved. This allowed spectral resonance assignment in a straightforward manner and the collection of a wealth of long‐range distance information. A high precision solid‐state NMR structure of microcrystalline ubiquitin was calculated with a backbone rmsd of 1.57 to the X‐ray structure and 1.32 Å to the solution NMR structure. Interestingly, we can resolve structural heterogeneity as the presence of three slightly different conformations. Structural heterogeneity is most significant for the loop region β1‐β2 but also for β‐strands β1, β2, β3, and β5 as well as for the loop connecting α1 and β3. This structural polymorphism observed in the solid‐state NMR spectra coincides with regions that showed dynamics in solution NMR experiments on different timescales.